Talent Management Strategy: Organizational Socialization - Phansaita, Nalinee; Kasai, Praweena; Charoonroj Na Ayudhya, Jatuphol (Dusit Thani College Journal, 2020)
Every organization nowadays aim to build their competitive advantage in which human resource is the valuable resource who will drive the organization to accomplish. The organization is not only developing their human resource to be competent but also facing the challenge in managing their talents. The objective of this article is to present the concept of Organizational Socialization and Talent Management strategy. The key findings of talent management emerging from the literature review focus on the recruitment of talent which mainly from internal source by considering from talent’s performance, leadership, attitude and the potential. The effective methods in talent’s training and development are job rotation, self-study program, job enlargement, special assignment to develop talent’s competency, domestic and overseas field trip, and specific training course. In addition, the talent’s motivation to contribute high effort to the organization is to apply fair and flexible performance based payment/reward. Finally, the talent retention can be done by giving an opportunity to learn and develop, idea sharing and innovative creation, giving a special assignment, building good relationship between supervisor and talent, and arranging favorable working environment which focuses on flexibility and work-life balance.